Описание концепта «Успех» в диалоге культур - Турчева, А.О. (My University, 2013)
The article is devoted to the description of the concept of "success" in the dialogue of cultures. Relevance of the study is to identify the specifics of the national linguistic world of all languages and cultures on the basis of comparative research on the material forming the special bi -speaking lexicographical sources. This fact actualizes the creation of special bilingual dictionaries of names of concepts. The author describes the theoretical basis of preparation of the Kazakh-Russian dictionary of names of concept on the example of the concept of "success."